2014
DOI: 10.2147/cia.s56683
|View full text |Cite
|
Sign up to set email alerts
|

Level of agreement between self-rated and clinician-rated instruments when measuring major depressive disorder in the Thai elderly: a 1-year assessment as part of the THAISAD study

Abstract: PurposeWhether self-reporting and clinician-rated depression scales correlate well with one another when applied to older adults has not been well studied, particularly among Asian samples. This study aimed to compare the level of agreement among measurements used in assessing major depressive disorder (MDD) among the Thai elderly and the factors associated with the differences found.Patients and methodsThis was a prospective, follow-up study of elderly patients diagnosed with MDD and receiving treatment in Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…immune system, 45 the stress buffering effect of social participation might protect the participants from developing hypertension. However, in this study, the GDS and SOC scores, which have been used in previous studies as proxies of psychological stress, 46,47 were not associated with hypertension, and also did not attenuate the association between participation in horizontal organizations and hypertension (Model 5 in Table 2). Moreover, emotional and instrumental social support was also not associated with hypertension and had no effect on the association between participation in horizontal organizations and hypertension (Model 2 in Table 2).…”
Section: Possible Mechanisms Linking Social Participation and Hypertecontrasting
confidence: 53%
“…immune system, 45 the stress buffering effect of social participation might protect the participants from developing hypertension. However, in this study, the GDS and SOC scores, which have been used in previous studies as proxies of psychological stress, 46,47 were not associated with hypertension, and also did not attenuate the association between participation in horizontal organizations and hypertension (Model 5 in Table 2). Moreover, emotional and instrumental social support was also not associated with hypertension and had no effect on the association between participation in horizontal organizations and hypertension (Model 2 in Table 2).…”
Section: Possible Mechanisms Linking Social Participation and Hypertecontrasting
confidence: 53%
“…The small number of men reporting moderate/severe depressive symptoms renders us statistically underpowered to interpret results in this group. The ability of the GDS-15 to detect symptoms of non-major depressive disorder may be limited (38), and relying on the GDS-15 as our sole assessment of depressive symptoms is a limitation particularly at baseline when consistency among depression screening tools is variable (39). Ideally, we would have adjusted for apolipoprotein ε4 (APOE4) status considering evidence that APOE4 modifies the relationship between depression and MCI risk (14); however, because APOE4 data was missing in 225 women and 128 men, we were statistically underpowered to do so.…”
Section: Resultsmentioning
confidence: 99%
“…Lazarus et al has indicated that if an event or a situation is considered stressful, it must work through cognitive processes [ 10 ]. The rising levels of stress can have harmful effects on one’s psychology, such as helplessness, sleeplessness, rumination, isolation, irascibility, triggering or aggravating anxiety and depression [ 9 , 11 ]. This will probably accelerate the development and progression of malignant diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has gradually shifted attention from negative predictors to exploration of the effects of positive constructs in cancer patients [ 11 , 14 , 15 ]. Promoting positive psychosocial outcomes is just as critical as minimizing negative ones.…”
Section: Introductionmentioning
confidence: 99%